2012
DOI: 10.1073/pnas.1213819110
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation pathway regulates T-cell function by targeting an adaptor protein Shc and a protein kinase Erk signaling

Abstract: NEDD8 (neural precursor cell expressed, developmentally downregulated 8) is a ubiquitin-like molecule whose action on modifying protein substrates is critical in various cellular functions but whose importance in the immune system is not well understood. Here we investigated the role of protein neddylation in regulating T-cell function using an in vivo knockdown technique. We found that reduced expression of Ubc12 in CD4 + T cells led to impaired T-cell receptor/CD28-induced proliferation and cytokine producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 14 publications
6
78
0
Order By: Relevance
“…Also, MLN4924 reduced MAPK signaling in inflammatory-elicited macrophages. These data are in accord with reports of MLN4924 effects on HIF-1α stabilization in microvascular endothelial cells (26) and MAPK activation in T cells, the latter linked to MLN-induced stabilization of SHC, a negative regulator of ERK signaling that was identified as a target for NEDDylation (67). Interestingly, the pathways identified in our study to be affected by MLN are linked with each other, e.g., reduced NF-κB activity, as observed upon MLN4924, was inversely linked with M2 polarization (68), and Arginase-1 has been reported to be regulated by HIF-2α (69), which is stabilized by NEDDylation (58).…”
Section: /Apoesupporting
confidence: 80%
“…Also, MLN4924 reduced MAPK signaling in inflammatory-elicited macrophages. These data are in accord with reports of MLN4924 effects on HIF-1α stabilization in microvascular endothelial cells (26) and MAPK activation in T cells, the latter linked to MLN-induced stabilization of SHC, a negative regulator of ERK signaling that was identified as a target for NEDDylation (67). Interestingly, the pathways identified in our study to be affected by MLN are linked with each other, e.g., reduced NF-κB activity, as observed upon MLN4924, was inversely linked with M2 polarization (68), and Arginase-1 has been reported to be regulated by HIF-2α (69), which is stabilized by NEDDylation (58).…”
Section: /Apoesupporting
confidence: 80%
“…12,13 Through its effects on protein neddylation, MLN4924 is known to have many effects including induction of DNA rereplication, apoptosis, autophagy, cell growth inhibition through p21-dependent senescence, and regulation of T-cell-mediated inflammatory response. [14][15][16][17][18] However, from a plasma cell biology perspective, MLN4924 can selectively inhibit the turnover of specific proteins which are targeted by CRLs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jin et al 20 have shown that the global inhibition of all CRL complexes through knocking down of Ubc12 inhibits neddylation and regulates T-cell functions. Our datadwhich used the pharmacological small-molecule inhibitor of neddylation, MLN4924, and a more targeted genetic approach of SAG À/À T cellsdconfirm and extend these observations.…”
Section: Discussionmentioning
confidence: 99%
“…8,18 Recent data have suggested that targeting neddylation with MLN4924 regulated the inflammatory functions of dendritic cells and macrophages, whereas inhibition of neddylation by knocking down Ubc12 mitigated CD4 T-cell responses. 1,19,20 Collectively, these studies point to an emerging role for neddylation in the regulation of immune cell subsets. However, the exclusive utilization of either the small molecule or the shRNA knockdown approaches does not rule out the possibility of potential off-target effects.…”
mentioning
confidence: 99%